Online dispute resolution: The future of justice - Mania, Karolina (International Comparative Jurisprudence, 2015)
The purpose of this study is to present the main facets of online dispute resolution, including a definition of the term, the types of resolution available, and the most recent legal regulations in this area. The article is an in-depth study of this field, discussing online mediation and electronic arbitration, their uses and their relationships with e-commerce. The strengths and weaknesses of online dispute resolution are identified and used to help formulate de lege ferenda stipulations. The paper is divided into three parts. Part I looks at preliminary aspects of online dispute resolution (ODR), including a definition of the term and an examination of its phases of development, implementation examples and the relationship between ODR and technology. Part II is devoted to examining the two most frequent forms of ODR: online mediation and electronic arbitration. Part III is an analysis of consumer disputes arising from commercial transactions made using electronic communications. As an example of the implementation of ODR, the author emphasises the importance of new European regulations on that and alternative dispute resolution (ADR): Directive 2013/11/EU of the European Parliament and of the Council of 21 May 2013 on alternative dispute resolution for consumer disputes and amending Regulation (EC) No 2006/2004 and Directive 2009/22/EC (Directive on consumer ADR), and Regulation (EU) No 524/2013 of the European Parliament and of the Council of 21 May 2013 on online dispute resolution for consumer disputes and amending Regulation (EC) No 2006/2004 and Directive 2009/22/EC (Regulation on consumer ODR).
Keywords: ADR; Alternative dispute resolution; Consumer dispute; E-commerce; Electronic arbitration; ODR; Online Dispute Resolution; Online mediation

Les conflits d'intérêts en arbitrage commercial international - Castres Saint Martin, Constance (Université Paris 2, 2015)
Le conflit d'intérêts est un sujet passionnant notamment en raison de son omniprésence dans l'actualité. Approximative, l'expression empruntée au magma lexical des politiciens et juristes anglo-américains s'est récemment diffusée en France dans le monde des affaires et aussitôt reprise par le jargon médiatique pour désigner des éventuelles interférences de l'intérêt privé dans l'exercice de pouvoirs de nature privée ou publique. Il n'existe en l'état actuel du droit positif français aucune réglementation spécifique de ces « conflits d'intérêts », pas plus en droit privé qu'en droit public, alors même qu'on se préoccupe de leur prévention tandis que leur sanction relève de qualifications plus générales. Il convient donc de s'interroger sur la définition et la valeur opératoire de cette notion et le régime juridique qui pourrait lui être réservé, ce que l'on se propose d'entreprendre dans la sphère du droit privé et par préférence dans le champ de l'arbitrage commercial, particulièrement exposé aux appétits hégémoniques des droits anglo-américains. Conflict of Interests is a fascinated subject due to its pervasiveness in the economic life. This approximated expression, borrowed from the politicians and Anglo-American lawyers' jargon, has recently spread into the French business world and was taken up by the media to designate the interferences of private interest in the exercise of powers of private or public nature. In the current state of French Law, there is no specific rule governing conflicts of interests, neither in Private Law, nor in Public Law. Indeed, politicians and scholars paradoxically only focus on their prevention, whereas their sanctions fall within the scope of broader notions. The aim of this research is to lay down the definition, the operative value and the regime of conflict of interests. The scope of this research shall be, within Private Law, Commercial Arbitration Law, which is particularly exposed to the hegemony of Anglo-American laws.
Keywords: Arbitrage; Arbitrage commercial international; Arbitragem; Arbitral abuses; Arbitration; Confiance légitime (droit); Confidence principle; Conflict of interests; Conflit d'intérêts; Conflits d'intérêts; Disclosure; Due process; Dérives arbitrales; Impartiality; Impartialité; Independence; Indépendance; Issue conflict; Justice arbitrale (administration); Principe de confiance; Procès équitable; Révélation; Transparence; Transparency

La médiation en santé : Contribution à une étude des conflits et des différends dans la relation de soins - Gibelin, Anne (Université de Montpellier, 2015)
La médiation peut se définir comme l’action de celui qui est médiateur et qui s’interpose entre deux ou plusieurs personnes pour résoudre un conflit ou un différend. Dans le domaine de la santé et plus particulièrement dans la relation de soins, des conflits et des différends peuvent survenir. La santé touche en effet à l’état des personnes, à leur intimité, à leur intégrité et les relations qui en découlent avec les professionnels de santé sont nécessairement empreintes d’une certaine sensibilité. C’est pourquoi ce secteur est considéré comme pourvoyeur potentiel de tensions. Il est donc intéressant d’étudier la résolution des conflits ou différends inhérents à la relation de soins, par un mode singulier et alternatif de règlement des différends : la médiation. L’étude de la nature juridique de ce processus est indispensable pour le différencier des autres modes alternatifs et exposer clairement ses forces et ses faiblesses. Ceci permettra ensuite de lui appliquer un régime juridique adéquat. En raison des manquements actuels, particulièrement au regard de l’encadrement du statut de médiateur, le constat d’un inévitable remaniement du régime de la médiation devra être effectué. Celui-ci devra impérativement allier souplesse et encadrement du mécanisme dans le but d’une efficacité optimale.
Keywords: Différends; Mediation; Médiation; Relation; Relations médecin-patient; Règlement de conflits; Santé; Soins

International Standards for Commercial Mediators - To, Christopher (University of Stirling, 2015)
This paper talks about the international standards for commercial mediators. It introduces the standards of eight different jurisdictions and afterwards, evaluates whether there should be one accrediting standard for all international commercial mediators. In the introduction chapter, the paper talks about the problems with the current legal system and then explains the growth of mediation in today’s society. By discussing the nature and practice of mediation, whether mediation should be compulsory or voluntary in light of Article 6 of the European Convention on Human Rights, rationale of the various jurisdictions covered, the paper then talks about the attributes that make a good mediator as well as the accreditation and training of mediators. From chapter two to chapter nine, the paper focuses on eight jurisdictions in which mediation is firmly enshrined within one legal culture to those that are just embarking on the concept (namely Australia, New Zealand, Indonesia, Malaysia, India, Hong Kong, California and Canada). Each chapter talks about the developments of commercial mediation, law and institutions as well as training and accreditation of mediators within their respective jurisdictions. In the concluding chapter, it discusses whether there should be one accrediting standard for international commercial mediators by exploring the advantages and disadvantages of having one accrediting standard as well as the author’s analysis and point of view on the subject.
Keywords: Commercial mediator; International standards; Mediation; Mediator; Médiateur

The Role of Arbitration Institutions in the Development of Arbitration in Africa - Onyema, Emilia (2015)
This conference which held at the premises of the African Union Commission, Addis Ababa on 23 July 2015 examined the functions of arbitration institutions in Africa. The conferenced discussions focused on sharing experiences by users and providers for the effective administration of arbitration references in the continent. The conference was organised by Dr Emilia Onyema of the School of Law, SOAS. KEY ARTICLES : - Regional Arbitration Institution for ECOWAS: Lessons from OHADA Common Court of Justice and Arbitration ; - The Role of Arbitration Institutions in the Development of Arbitration in Africa ; - “Africa’s Century” – The rise of International Arbitration in Africa and what it means for users of Arbitral Institutions in Africa ; - Reawakening Arbitral Institutions for Development of Arbitration in Africa ; - Opening Up International Arbitration in Africa ; - Africa as a Viable Space for Arbitration: Role of National Courts and Laws - The Role of Counsel in Promoting African Arbitral Institutions ;
Pages: 1-160
Keywords: Africa; Arbitrage; Arbitragem; Arbitration; Conference

Disputes in the Digital era : the evolution of dispute resolution and the model ODR system - Lekkas, Zissis (Université Toulouse 1 Capitole, 2015)
Le sujet de la thèse est la résolution en ligne des litiges (ODR) et l'objectif de la thèse est de proposer un modèle de système ODR basé sur l'expérience du mouvement de résolution des différends. ODR n’est pas un phénomène isolé de ces derniers temps, mais en raison de l'évolution des conflits et la résolution des différends. Initialement, les différends survenus entre les parties à la proximité géographique et pour laquelle les tribunaux traditionnels sont le principal moyen de résolution. Cependant, comme les gens ont commencé à voyager de plus grandes distances et de communiquer de loin, les conflits ont évolué comme ils ont augmenté en nombre, sont devenus frontière plus complexe et de plus en plus transversale. Résolution des différends évolués en règlement des différends parallèle et alternatif (ADR) a été utilisée. Cependant, les conflits ont évolué une fois de plus quand le monde est entré dans l'ère numérique. Non seulement les conflits sont devenus encore plus transfrontalier, mais de nouveaux conflits sont apparus qui proviennent exclusivement dans le cyberespace. Afin de satisfaire aux exigences de l'ère numérique, la résolution des différends fit sortir le concept de l'ODR. ODR est née de la combinaison de l'ADR et de la technologie de l'information et de la communication (TIC) de l'ère numérique. D'autres moyens de règlement des différends ont été transférés dans le monde virtuel et ont donné naissance à la résolution des litiges en ligne. ADR et ODR sont examinés largement, et l'examen comprend leurs concepts, leur origine, les principales formes de négociation, de médiation et d'arbitrage et leurs équivalents en ligne, ainsi que leurs avantages et leurs inconvénients. La thèse illustre l'évolution des conflits et la résolution des différends de l'ère analogique, lorsque la résolution des différends était face à face, à l'ère du numérique, lorsque les différends sont réglés dans le cyberespace. Il démontre que l'ODR est une nécessité de l'ère numérique, mais aussi qu'il a le potentiel pour être un moyen révolutionnaire, efficace et réussi à résoudre les différends; d'une manière qui sera l'avenir de la résolution des différends. Sur la base de l'expérience accumulée par l'examen de l'évolution de la résolution des différends et sur ? Lla base des conclusions tirées, la thèse formule une proposition pour le système ODR. La thèse décrit le système ODR, de son processus en trois étapes et la nécessité de l'arbitrage en ligne, sur le réseau ODR, la régulation du système ODR, l'architecture technologique des fournisseurs ODR, leur financement, ainsi que les mesures nécessaires de la sensibilisation et la confiance afin que ODR remplit son plein potentiel.
Keywords: Arbitrage; Arbitragem; Arbitration; Commerce électronique; Modes électroniques de règlement des litiges; Online Dispute Resolution; Système ODR

A arbitragem em juízo - Valença Filho, Clávio de Melo (Universidade de São Paulo, 2015)
Situado no centro do sistema jurídico transnacional da lex mercatoria, o árbitro é autoridade estrangeira em relação ao juiz nacional do foro. O sistema da lex mercatoria se distingue do nacional pela sensibilidade de suas reações aos ruídos provenientes do sistema da economia, não pelo vinculo a território. O árbitro não tem foro, tem setor; fora dele, a arbitragem se adapta mal. Por impor limites à função jurisdicional do Estado-juiz, a convenção de arbitragem constitui regra de competência internacional do juiz do foro e, de competência internacional indireta do árbitro e dos juízes estrangeiros. Profere sentença inexistente o juiz nacional que atropela as regras de sua jurisdição internacional. Também não ingressam no sistema do foro as decisões proferidas por quem não se adeque às regras de jurisdição internacional indireta do foro. Isso ocorre quando a sentença arbitral ou o julgamento estrangeiro em lide cujo objeto é a própria arbitragem agridem a intensidade que o foro atribui aos efeitos negativos da competência-competência e da convenção de arbitragem. O efeito negativo da competência-competência não decorre da convenção de arbitragem, mas da proteção que o ordenamento outorga à mera aparência. Os efeitos da convenção de arbitragem dizem respeito ao mérito das lides, o negativo e o positivo. Aquele, como o negativo da competência-competência, ostenta natureza de direito público subjetivo. Este, de direito privado subjetivo. Todos constituem direito subjetivo em sentido técnico, na medida em que permitem provocar o Estado-juiz com o fito de apoiar a instauração da instância ou assegurar o afastamento do próprio Estado-juiz. O paralelismo processual tem origens distintas segundo ocorra entre autoridades vinculadas ao mesmo sistema ou a sistemas distintos. Na primeira hipótese, decorre de error in judicando; na segunda, é consequência natural da ausência de harmonia entre os sistemas. Entre árbitro e juiz, não se resolve com remédios concebidos para o conflito de competências, como a litispendência ou o incidente constitucional perante o STJ. Só uma estrutura convencional de acoplamento entre sistemas permitiria a harmonização. Já o efeito negativo da convenção de arbitragem pode ser mitigado em função de risco de denegação de justiça, para devolver ao Estado-juiz a jurisdição de urgência ou a necessária ao julgamento de pretensões do devedor em dificuldades. A abertura da falência não interfere na capacidade do credor ou na natureza de seus bens ou direitos, não suspende a tramitação da arbitragem e não impede a instauração de novas instâncias. É válida a convenção de arbitragem estipulada após a falência e a massa tem o direito de participar da arbitragem, junto com o devedor. The transnational legal system of lex mercatoria is not linked to a given territory. Its differentiation from the civil justice system is based upon its capacity to react to the needs of the economy. The fact that the arbitrator is positioned in the center of the lex mercatoria system makes the arbitrator foreign to the courts and its legal system. By imposing limits upon the jurisdictional State function, the arbitration agreement and its regulation serves as an international jurisdiction rule for the forum court. It also works as an indirect international jurisdiction rule through which the national court inspects the jurisdiction of an arbitrator or a given foreign court. National courts decisions that are rendered in disregard of international jurisdiction rules are non-existent. Foreign decisions that are incompatible with indirect international jurisdiction rules must be set aside by the forum courts. This is the case when arbitral awards and foreign judgments related to arbitration are disrespectful to the forum criterions binding the negative effect of the competence-competence and to the negative effect of the arbitration agreement. The negative effect of competence-competence is not a consequence of the agreement to arbitrate, but of the protection that the legal system gives to its mere appearance. The effects of the arbitration agreement concern the merits of the disputes, the negative and the positive. The former, as well as the negative effect of the competence-competence principle, are in nature of subjective public law. The latter is of the nature of subjective private law. All constitute subjective rights in the technical sense, in the way in which they allow the court system to support the commencement of proceedings or to ensure the removal of the national courts. Procedural parallelism has different origins depending upon whether it occurs among arbitrator and courts belonging to the same legal system of the court deciding the conflict or to a different one. In the first hypothesis, it originates from error in judicando; in the second, it is a natural consequence of the lack of harmony between the systems. Between arbitrator and judge, such lack of harmony cannot be resolved through the remedies created to address jurisdictional conflict, such as lis pendens or the constitutional incident before Brazils STJ. Only by coupling different legal systems through conventional structure would harmonization arise. The negative effect of the arbitration agreement is mitigated by conferring upon courts jurisdiction for the grant of interim and provisional measures based on the risk of denial of justice. By its turn, a bankruptcy filing does not interfere with the creditors capacity nor with the nature of its assets or rights, and it does not suspend the arbitration proceeding or the commencement of new proceedings. The agreement to arbitrate after the initiation of bankruptcy proceedings is valid and the estate-in-bankruptcy may participate in the arbitration along with the debtor.
Keywords: Arbitrage; Arbitragem; Arbitration; Arbitrator; Arbitre; Argentina; Bankruptcy; Brasil; Civil Procedure; Conflict of jurisdictions; Direito comparado; Estados Unidos; Falência; França; Insolvency; Judge; Lex mercatória; Processo civil; Urgent measures

Economic and Empirical Analysis of Contractual Dispute Resolution - Miller, Samuel Mark (Vanderbilt University, 2015)
This dissertation uses Python-based programming to retrieve and analyze a sample of approximately 400,000 material contracts that companies filed with the Securities and Exchange Commission between 2001 and 2013, focusing on the dispute resolution mechanisms specified therein. The first chapter considers the effectiveness of two state-level efforts to attract dispute resolution business, examining how specialized “business courts” and the Revised Uniform Arbitration Act affected arbitration and choice-of-forum clause use in these material contracts. The second chapter examines whether and how companies and executives “customized” their arbitration clauses in response to Internal Revenue Code Section 409A, which increased both the likelihood and the complexity of potential disputes between these parties. The third chapter considers how companies and executives responded when the Supreme Court overturned the Ninth Circuit’s anomalous refusal to enforce employment-related arbitration clauses. Each chapter finds that contracting parties adjusted their dispute resolution provisions in response to the policy change(s) at issue – suggesting that for the sophisticated parties in my dataset, these provisions receive careful thought and are not mere “boilerplate.”
URI: http://hdl.handle.net/1803/11146
Keywords: Arbitrage; Arbitragem; Arbitration; Contracts; Dispute resolution; Econometrics

Arguments in favour of reconceptualising the fair and equitable treatment (FET) standard in international investment arbitration : developing countries in context - Islam, Rumana (University of Warwick, 2015)
The Fair and Equitable Treatment (FET) standard is the most important and, because of its flexible nature and its status as a ‘catch-all’ provision, most controversial investment protection standard in international investment treaties. The standard imposes the most far-reaching obligation of any aspect of such treaties. This thesis’ core contention is that the current investment tribunals’ interpretation of the FET standard prioritises the interests of foreign investors and neglects the perspectives of host developing countries. Therefore there is a pressing need to reconceptualise the interpretation of the FET standard. In service to depicting the perspectives of host developing countries, this thesis advances an understanding of classifications such as ‘developing’ and ‘developed’ that reflects the issues and challenges that these countries face in the investment dispute context, such as their lack of resources, administrative capacity, technology, and infrastructure, as much as the economic and social level of development international organisations generally emphasise in their classifications. It addresses socio-political circumstances such as political instability, social unrest, conflict and its aftermath, social and political transition, and economic crises and their impact on host developing countries in the investment dispute context. Through a detailed study of the approaches they have taken to such issues in their interpretation of the breach of FET standard in disputes involving host developing countries, it shows that current investment tribunals have taken inconsistent and inadequate approaches to the issues host developing countries face. It argues that a reconceptualised interpretation of the FET standard which acknowledges the developmental issues and challenges this thesis has identified would accommodate the needs of the host developing countries while continuing to give reasonable protections to foreign investors and therefore serve the needs of the system as a whole.
URI: http://webcat.warwick.ac.uk/record=b2766071~S1
Keywords: Arbitrage; Arbitragem; Arbitration; Arbitration and award; Developing countries; Dispute resolution (Law); Equity; Foreign investment; Free trade agreemtment; International business enterprises; Investments; Unfair competition

Partes e terceiros na arbitragem - Costa, Guilherme Recena (Universidade de São Paulo, 2015)
A tese discute o problema dos terceiros na arbitragem. Ela distingue os planos substantivo (contratual) e processual (jurisdicional) da arbitragem e, portanto, o status de parte e terceiro com relação, respectivamente, à convenção de arbitragem e ao processo arbitral. Depois de desenvolver as premissas teóricas na Parte 1, a Parte 2 expõe as teorias contratuais e societárias por meio das quais um não-signatário pode ficar vinculado à convenção de arbitragem, com destaque para a extensão a todos os acionistas da companhia da cláusula compromissória estatutária, bem como para a aplicação do princípio da boa-fé objetiva (teoria dos atos próprios, estoppel) para impedir com que determinados signatários burlem a convenção de arbitragem ao incluir terceiros no polo passivo da demanda ou, ainda, para impor a arbitragem a não-signatários que derivaram um benefício do contrato inter alios. Na Parte III, a atenção volta-se para o processo e a sentença arbitral. Expõe-se uma teoria dos efeitos da sentença, buscando-se explicar a sua potencial eficácia ultra partes com base: a) na necessidade de realizar o direito da contraparte à tutela jurisdicional (adquirente do direito litigioso, sucessores post rem judicatam); e b) na identificação de nexos de prejudicialidade-dependência permanente entre as relações jurídicas no plano do direito material (terceiro titular de situação dependente). Refutam-se, em passo seguinte, teorias que preconizam o valor absoluto da sentença. Oferece-se, como núcleo da tese, uma reconstrução dogmática das modalidades de intervenção de terceiro, buscando adaptá-las à arbitragem para alcançar, em cada situação, um justo equilíbrio entre as expectativas contratuais das partes originárias e a natureza privada da arbitragem, de um lado, e os efeitos da sentença perante terceiros, de outro. Conclui-se que, em alguns casos, legitima-se o terceiro a intervir voluntariamente, mesmo contra ou independentemente da vontade das partes, se ele estiver sujeito aos efeitos da sentença. Em hipótese excepcionalíssimas, ademais, a parte pode sujeitar um terceiro aos efeitos de intervenção, provocando a sua assistência no processo arbitral. The thesis addresses the problems of third parties in arbitration. It distinguishes the substantive (contractual) and procedural dimensions of arbitration and, hence, the status of parties and third parties in connection with, respectively, the arbitration agreement and the arbitral proceedings. After spelling out theoretical premises in Part 1, Part 2 covers the contractual and corporate theories by which a non-signatory may be bound by the arbitration agreement, highlighting the extension to all shareholders of the agreement in the corporate bylaws, as well as the application of the equitable doctrine of estoppel to bar certain signatories from avoiding the arbitration agreement by including third parties as defendants or even to impose arbitration onto non-signatories who derived a benefit from the contract inter alios. In Part III, my attention turns to the proceedings and the arbitral award. I set out a doctrine of the effects of judgments, seeking to explain their potential effects on third parties based: a) on the prevailing need to preserve the counterpartys right to a binding declaration on its asserted claims (acquirers, successors post rem judicatam); b) the identification of substantive ties between legal relationships that make the third parties rights permanently dependent on the situation between the parties. I then refute theories ascribing absolute value to the award vis-à-vis third parties. As the core of the thesis, I offer a doctrinal reconstruction of third party interventions, seeking to adapt them to arbitration in order to achieve, in each situation, a fair balance between the contractual expectations of the original parties and the private nature of arbitration, in one hand, and the effects of the award on third parties, on the other. I conclude that a third party should be allowed to intervene, albeit against the will of the parties, if it is subject to the concrete effects of the arbitral award. In exceptional situations, moreover, a party may vouch in a third party, who will then be bound by the determinations of factual and legal issues made in the award.
Keywords: Arbitrage; Arbitragem; Arbitration; Arbitration Agreement; Coisa julgada; Direito processual civil; Effects of arbitral awards; Non-signatories; Third parties; Third party intervention; Tierces parties

Convergence of international trade and investment law in practice : how should investor-state arbitral tribunals engage with trade norms? - Chevry, Jonathan (European University Institute, 2015)
This thesis aims to provide an analytical framework to which investor-State arbitral tribunals can refer in cases where international trade law is invoked. The starting point of the present study is the trend in commentary on international trade and investment law, which makes the argument that international trade and investment law should be reconciled due to the clear "convergence" between (some of) their constitutive elements. This convergence argument is not misguided: there are similarities between the underlying principles of global trade and investment and, as such, a better coordination of these principles would be helpful for several reasons. Such reasons include legal certainty, reduction of transaction costs, better coherence in the operation of international agreements that now combine both trade and investment provisions, to name a few. However, no matter how reconcilable or converging the two disciplines may be, their enforcement mechanisms are structurally different and are likely to remain so even if the reforms towards a modernization of the investment dispute settlement (currently discussed at the EU policy level) are eventually implemented in the near future. In light of this last point, it is possible to claim that integration between trade law and investment law will only have limited or even negative effects if the trade and investment adjudicators continue to exercise their functions in an isolated manner, without taking cognizance of (i) the norms contained in the other discipline and (ii) the other adjudicator's scope of authority. Effective convergence of trade and investment entails a two-way process pursuant to which one adjudicator can use (i.e. take into account, refer to, apply, interpret and enforce) the law of the other and vice-versa. The thesis envisages one of the two dimensions of this process, namely the use of trade law by the investment adjudicator. Looking into the details of the convergence argument, the role of investment dispute settlement mechanism and the use of trade norms over the past two decades by litigants and arbitrators, the present study identifies both the legal techniques and obstacles these actors shall apply or go beyond in order to use trade norms in the most appropriate way and, more importantly, benefit from this use.
Accepted: 2015-12-09T14:30:56Z
Keywords: Arbitrage; Arbitragem; Arbitration; Foreign investment; Foreign trade regulation; International commercial arbitration

Milletlerarası ticari tahkimde hakemlerin bağımsızlığı ve tarafsızlığı - Kayali, Di̇dem (Ankara Üniversitesi, 2015)
Milletlerarası ticarî sözleşmelerden kaynaklanan uyuşmazlıklar söz konusu olduğunda akla ilk gelen çözüm yöntemi tahkimdir. Zira milletlerarası ticarî tahkimin devlet yargılamasına göre önemli avantajları bulunmakta, hakemlerin bağımsızlığı ve tarafsızlığı ise bu avantajların en önemlilerinden biri olarak karşımıza çıkmaktadır. Bu çerçevede, tahkim süreci başlarken hakemlerin bağımsız ve tarafsız olmaları ile süreç tamamlanana kadar bu şekilde kalmaları gerektiği hususu milletlerarası ticarî tahkimin en temel ilkesi olarak genel kabul görmüş; millî kanunlarda, milletlerarası metinlerde ve milletlerarası tahkim kurumlarının düzenlemelerinde doğrudan ya da dolaylı bir şekilde yerini almıştır. Bu çalışmada da bağımsızlık ve tarafsızlık kavramlarından ne anlaşılması gerektiği, bu kavramların uygulamada nasıl yorumlandığı, tahkim yargılamasındaki önemi ve nasıl korunduğu, yukarıda bahsedilen düzenlemeler ile millî mahkemeler ve milletlerarası tahkim kurumlarının kararları ışığında incelenmiştir. When disputes emerging from international commercial contracts are in question, arbitration is the first resolution method that comes to mind. This is because international commercial arbitration has significant advantages compared to the state jurisdiction where impartiality and independence of arbitrators is considered to be one of the most important ones of those advantages. In this framework, the necessity that arbitrators ought to be impartial and independent from the very start till the end of the arbitration process has gained general acceptance as the basic principle of international commercial arbitration and directly or indirectly has taken its place in national laws, international texts and regulations of international arbitration institutions. In this study, the meaning of independence and impartiality, how they are interpreted in practice, the importance of these concepts in international commercial arbitration and how they are protected are examined in the framework of above mentioned regulations and decisions of national courts and international arbitration institutions.
393376
Keywords: Arbitrage; Arbitration; Arbitrators; Arbitre; Bağımsızlık; Hakemler; Impartiality; Impartialité; Independence; International Arbitiation Law; International Trade; International disputes; Milletlerarası Tahkim Kanunu; Tahkim; Tarafsızlık; Uluslararası ticaret; Uluslararası uyuşmazlıklar

Building legal bridges: fostering eastern Africa integration through commercial arbitration - Muigua, David K. (Alternative Dispute Resolution, 2015)
This paper explores the feasibility of commercial arbitration as a means to foster the process of Eastern Africa integration. The author proffers an argument in the context of Eastern Africa integration, that commercial arbitration offers a better platform for dealing with commercial disputes that are bound to arise considering the differing personal or state interests in the ongoing Eastern Africa integration, as compared to national Courts. This discourse is premised on the fact that the five member countries making up the East African Community (EAC) have different legal systems and this presents a major challenge in harmonising the various legal systems. This also affects the possible use of courts in managing the potential transnational commercial disputes due to the potentially different rules of procedure and practice. The paper briefly examines the state of commercial arbitration in the EAC Member States with a view to identifying the existing frameworks and any impediments in their effectiveness. Finally, the author makes a case for utilizing commercial arbitration to build bridges and foster Eastern Africa integration for development.
http://erepository.uonbi.ac.ke/handle/11295/81712
Keywords: Arbitrage; Arbitragem; Arbitration; Commercial Arbitration

Convention on the Recognition and Enforcement of Foreign Arbitral Awards (New York, 1958) - UNCITRAL (United Nations, 2015)